FORMATION OF THE BASIC RULES OF THE HANDBALL SPORT TRAINING SYSTEM - Juraboyev M. M. (Bright Mind Publishing, 2025)
The system of sports training for handball players includes various aspects that help athletes achieve high results in this game. In sports training, athletes have physical training, tactical training, and technical training.
Keywords: Handball, federations, sports, competitions, skills, cooperation, coaching, training, sports schools. Sports, technology, professional sports, tactical training, technical training, motivation, physical training, attack, defense.